The Influence Of E-WOM and Risk Perception On The Decision To Visit Bojonegoro Starfruit Garden Agrotourism During The Covid_19 Pandemic - Silvi Dwi Tatiani; Anik Lestari Andjarwati (Profesional Muda Cendekia Publishing, 2022)
Tourism is the fastest growing industry. Along with the progress of the times, the need for travel is increasing. Since the beginning of 2020, covid_19 has hit the world, one of the sectors that is feeling the impact of this pandemic is the tourism sector. This study discusses the influence of electronic word of mouth and risk perception on the decision to visit the Bojonegoro starfruit agrotourism during the covid_19 pandemic. The sample used in this study were 200 respondents aged 16-60 years. The sampling method used is judgmental sampling using a Likert scale as a measuring tool. The data analysis technique used in this research is multiple linear regression analysis. The results showed that the electronic word of mouth variable had a significant effect on the visiting decision, while the risk perception variable had no significant effect on the visiting decision. The result of the study can be used as consideration for agrotourism to increase promotion through the internet to improve tourist visiting decisions.